2019
DOI: 10.1371/journal.pone.0212789
|View full text |Cite
|
Sign up to set email alerts
|

General cognitive but not mathematic abilities predict very preterm and healthy term born adults’ wealth

Abstract: ObjectiveVery preterm (<32 weeks gestation; VP) and/or very low birth weight (<1500g; VLBW) children often have cognitive and mathematic difficulties. It is unknown whether VP/VLBW children’s frequent mathematic problems significantly add to the burden of negative life-course consequences over and above effects of more general cognitive deficits. Our aim was to determine whether negative consequences of VP/VLBW versus healthy term birth on adult wealth are mediated by mathematic abilities in childhood, or rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
(66 reference statements)
2
6
0
3
Order By: Relevance
“…2 They are also important predictors of later educational outcome, social status, and wealth in both very preterm and term children. 3 The findings by Benavente-Fernández et al 1 are consistent with results from a 2015 systematic review, 4 which showed that a low level of parental education is among the strongest predictors of poor overall cognitive outcomes in very preterm children. Similarly, the adverse association of moderate to severe brain injury with intelligence from childhood to adulthood has been consistently reported in longitudinal studies.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…2 They are also important predictors of later educational outcome, social status, and wealth in both very preterm and term children. 3 The findings by Benavente-Fernández et al 1 are consistent with results from a 2015 systematic review, 4 which showed that a low level of parental education is among the strongest predictors of poor overall cognitive outcomes in very preterm children. Similarly, the adverse association of moderate to severe brain injury with intelligence from childhood to adulthood has been consistently reported in longitudinal studies.…”
supporting
confidence: 55%
“…11 And still, these children are less likely to achieve the SES of their parents and show poorer outcomes on markers of wealth, such as educational level, income, and employment. 3,12 Furthermore, although there is consistent evidence that improved parenting and improved early education (often delivered together) improve long-term cognitive and academic outcomes in term children with socioeconomic disadvantage, 13 the same has not been found for those born with very low birth weight or of very low gestational age. 14 Where do we go from here?…”
mentioning
confidence: 99%
“…Indeed, general cognitive abilities were found to predict adult wealth in a study of very preterm and/or very low birth weight, with the very preterm and/or very low birth weight adults also having significantly lower wealth than the term-born controls. 31 Previous research by the EPICure study group has revealed that EP children are at markedly high risk of poor academic attainment 32 and that cognitive ability is a predictive factor. 33 Sixteen percent of the EP participants scored in the intellectual disability range (IQ ,70) at 19 years.…”
Section: Neuropsychological Outcomes At 19 Yearsmentioning
confidence: 99%
“…Im Rahmen von einzelnen Studien wie z. B. der Bayerischen Entwicklungsstudie (BESt) (Jaekel, Baumann, et al, 2019;Jaekel, Sorg, et al, 2019) sind sehr gut dokumentierte deutsche Daten bis ins Erwachsenenalter, verfügbar. Seit 2009 existiert zudem der Forschungsverbund des German Neonatal Network (GNN) an dem mehr als 50 größere Zentren beteiligt sind (Herting et al, 2020;Humberg et al, 2020).…”
Section: Frühgeburt Und Langfristige Folgenunclassified